2010
DOI: 10.1038/nchem.901
|View full text |Cite
|
Sign up to set email alerts
|

Guest-induced growth of a surface-based supramolecular bilayer

Abstract: Self-assembly of planar molecules on a surface can result in the formation of a wide variety of close-packed or porous structures. Two-dimensional porous arrays provide host sites for trapping guest species of suitable size. Here we show that a non-planar guest species (C(60)) can play a more complex role by promoting the growth of a second layer of host molecules (p-terphenyl-3,5,3″,5″-tetracarboxylic acid) above and parallel to the surface so that self-assembly is extended into the third dimension. The addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
124
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 22 publications
(36 reference statements)
2
124
0
2
Order By: Relevance
“…Reported dimensional errors are derived from a statistical evaluation of multiple molecular spacings. Some previous work has considered the co-assembly of C 60 and p-conjugated oligomers (e.g., oligothiophenes [51][52][53] and sexiphenyl [54][55][56]) on single crystal metal surfaces, and demonstrated that H-bond directed p-conjugated assembly can dictate the solid state arrangement of C 60 on surfaces [57][58][59][60][61][62][63][64][65][66][67]. Resulting C 60 overlayer structures have included dimerization at high coverage on anthracene carboxylic acid layers on Ag(1 1 1) [59,64,65], and dimeric and hexameric clusters residing within various supramolecular assemblies of perylene tetracarboxylic diimide and melamine on Au(1 1 1) [61][62][63]66].…”
Section: Assembly On a Mebqph Monolayermentioning
confidence: 99%
“…Reported dimensional errors are derived from a statistical evaluation of multiple molecular spacings. Some previous work has considered the co-assembly of C 60 and p-conjugated oligomers (e.g., oligothiophenes [51][52][53] and sexiphenyl [54][55][56]) on single crystal metal surfaces, and demonstrated that H-bond directed p-conjugated assembly can dictate the solid state arrangement of C 60 on surfaces [57][58][59][60][61][62][63][64][65][66][67]. Resulting C 60 overlayer structures have included dimerization at high coverage on anthracene carboxylic acid layers on Ag(1 1 1) [59,64,65], and dimeric and hexameric clusters residing within various supramolecular assemblies of perylene tetracarboxylic diimide and melamine on Au(1 1 1) [61][62][63]66].…”
Section: Assembly On a Mebqph Monolayermentioning
confidence: 99%
“…These molecular networks, which can be formed through selfassembly processes on a variety of different substrates including semiconductors 5,6 , metals 7,8 , insulators [9][10][11] and layered materials [12][13][14][15] , are, in almost all cases, limited to monolayer thickness. Progress towards the growth of higher layers has so far been much more limited, with demonstrations of bilayer growth 16,17 and site-specific molecular adsorption 5,[18][19][20][21][22][23][24] . Specifically, the additional functional control, which may be achieved through the formation of heterostructures realized by placing one supramolecular layer on another and resulting in growth into the third dimension perpendicular to the substrate, has not been widely explored for these materials.…”
mentioning
confidence: 99%
“…Here we show that cyclic porphyrin polymers, with molecular weights of 30-60 kDa, self-assemble into nested structures on a gold surface. These nested assemblies are only observed when the cyclic polymer has 30 or more repeat units, in keeping with the predictions of a simple geometrical model.The importance of non-covalent self-assembly in biology has inspired many studies of supramolecular organisation on surfaces [6][7][8] , generating 2D assemblies with progressively escalating complexity, from early work on simple structures such as clusters 9 and rows 10,11 , to nanoporous arrays 12,13 , host-guest architectures [14][15][16] , hierarchical arrangements 17 , and multicomponent assemblies [17][18][19] . However, cooperative conformational control has proved difficult to achieve, and this remains a significant gulf between artificial and biological systems.…”
mentioning
confidence: 99%
“…The importance of non-covalent self-assembly in biology has inspired many studies of supramolecular organisation on surfaces [6][7][8] , generating 2D assemblies with progressively escalating complexity, from early work on simple structures such as clusters 9 and rows 10,11 , to nanoporous arrays 12,13 , host-guest architectures [14][15][16] , hierarchical arrangements 17 , and multicomponent assemblies [17][18][19] . However, cooperative conformational control has proved difficult to achieve, and this remains a significant gulf between artificial and biological systems.…”
mentioning
confidence: 99%